Origin, maintenance and spread of antibiotic resistance genes within plasmids and chromosomes of bloodstream isolates of Escherichia coli. Issue 4 (11th April 2020) - Goswami, Cosmika; Fox, Stephen; Holden, Matthew T.G.; Connor, Martin; Leanord, Alistair; Evans, Thomas J.
Abstract : Blood stream invasion by Escherichia coli is the commonest cause of bacteremia in the UK and elsewhere with an attributable mortality of about 15–20 %; antibiotic resistance to multiple agents is common in this microbe and is associated with worse outcomes. Genes conferring antimicrobial resistance, and their frequent location on horizontally transferred genetic elements is well-recognised, but the origin of these determinants, and their ability to be maintained and spread within clinically-relevant bacterial populations is unclear. Here, we set out to examine the distribution of antimicrobial resistance genes in chromosomes and plasmids of 16 bloodstream isolates of E. coli from patients within Scotland, and how these genes are maintained and spread. Using a combination of short and long-read whole genome sequencing methods, we were able to assemble complete sequences of 44 plasmids, with 16 Inc group F and 20 col plasmids; antibiotic resistance genes located almost exclusively within the F group. bla CTX-M15 genes had re-arranged in some strains into the chromosome alone (five strains), while others contained plasmid copies alone (two strains). Integrons containing multiple antibiotic genes were widespread in plasmids, notably many with a dfrA7 gene encoding resistance to trimethoprim, thus linking trimethoprim resistance to the other antibiotic resistance genes within the plasmids. This will allow even narrow spectrum antibiotics such as trimethoprim to act as a selective agent for plasmids containing antibiotic resistance genes mediating much broader resistance, including bla CTX-M15 . To our knowledge, this is the first analysis to provide complete sequence data of chromosomes and plasmids in a collection of pathogenic human bloodstream isolates of E. coli . Our findings reveal the interplay between plasmids and integrative and conjugative elements in the maintenance and spread of antibiotic resistance genes within pathogenic E. coli .